Effects of Saint John’s Wort extract on intestinal injury and apoptosis (Annals of Medical Research, 2021)
Aim: Reactive oxygen species play an important role in the pathophysiology of intestinal ischemia/reperfusion (I/R) injury by causing apoptosis. The present study aimed at exploring the possible protective effect of Saint John’s Wort (SJW) extract in I/R injury.Materials and Methods: Twenty four healthy male Wistar rats of 6 to 8 weeks old weighting averagely 200 to 250 g were studied. They were fed on standard rat food and drinking water at room temperature with 12/12 hours periods of day and night. SJW (300 mg/kg, peroral) or saline was given by oral route for 3 days prior to ischemia, 30 minutes before the ischemia, and just before reperfusion. To the rats in the control group, sham operation and application of saline were done. Levels of TNF-α, IL-1β and LDH were measured in the serum samples. In the small bowel tissue, levels of malonaldehyde (MDA) and glutathione (GSH) and activity of myeloperoxidase (MPO) and Na-K ATPase and level of caspase-3/β-actine and Bcl-2/β-actine were measured.Results: I/R increased serum levels of LDH, TNF-α and IL-1β, small bowel level of MDA and MPO whereas it decreased level of GSH and activity of Na-K ATPase in the small bowel tissue. The level of caspase-3/β-actine increased while the level of Bcl-2/β-actine decreased in the I/R group compared to the controls. With the application of SJW, these values approached the control levels.Conclusion: These results indicate that SJW recovers small bowel function by reducing oxidation injury during I/R.
Keywords: Apoptosis; intestinal injury; ischemia; reperfusion; Saint John’s Wort